KEBERDAYAAN ANGGOTA KELOMPOK TANI DALAM MENERAPKAN GOOD HANDLING PRACTICES (GHP) PADI SAWAH DI DESA SINDANGGALIH KECAMATAN CIMANGGUNG KABUPATEN SUMEDANG - Dwinggi Guswita; Maspur Makhmudi; Kusmiyati Kusmiyati (Jurnal Inovasi Penelitian, 2020)
Abstract Extensive rice production invites a variety of problems, especially in the harvest and postwar processes. Many times over the harvesting does not end in their capacity. Crop loss resulting from failure in management is still the dominant culture that dominates agricultural activity. This, of course, is a new problem because it would affect the income of farmers in enormous Numbers and in considerable Numbers. Moreover, the quality produced without a good post-harvest prsoses would significantly affect the quality of the production itself. An alternative solution to address the problem was aimed at empowering farmers in the implementation of good handling practices (GHP), and of course, would increase the more specialized farmers' bargaining in the economic, social and sustainable areas of the agricultural culture in the agricultural communities themselves.